2003
DOI: 10.1152/ajprenal.00311.2002
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant ameliorates cisplatin-induced renal tubular cell death through inhibition of death receptor-mediated pathways

Abstract: We have recently demonstrated the direct involvement of the death receptor-mediated apoptotic pathways in cisplatin-induced renal tubular cell (RTC) death. Reactive oxygen species are thought to be a major cause of cellular damage in such injury. The aim of this study was to examine the mechanism through which antioxidants ameliorate cisplatin-induced RTC death, with special emphasis on death receptor-mediated apoptotic pathways. Cisplatin was added to cultures of normal rat kidney (NRK52E) cells or injected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
65
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 56 publications
8
65
1
2
Order By: Relevance
“…Thus, oxidative stress and death receptor-mediated apoptotic cascades are considered to interact synergistically. 36,37 Nonsignificant alterations of renal MDA and thiol content may be due to low dose of cisplatin. PSO administration 1 h before cisplatin treatment significantly reduced the development of cisplatin-induced acute renal failure as evidenced by functional and histopathological findings.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, oxidative stress and death receptor-mediated apoptotic cascades are considered to interact synergistically. 36,37 Nonsignificant alterations of renal MDA and thiol content may be due to low dose of cisplatin. PSO administration 1 h before cisplatin treatment significantly reduced the development of cisplatin-induced acute renal failure as evidenced by functional and histopathological findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, dialysis itself cannot repair the RTEC. Some reagents, such as fosfomycin (34,35), anti-TNF (36), and antioxidants (37), have been reported to have the ability to protect RTEC from noxious substances. From our results, we suggest that the mobilization of BMC by G-CSF, etc., could become a new strategy for preventing not only acute renal failure as a result of the necrosis of RTEC but also the side effects of drugs on various organs.…”
Section: Discussionmentioning
confidence: 99%
“…11,29) In the previous study, various antioxidant agents showed protective effect against renal injury induced by cisplatin in rats. [30][31][32] In summary, butein, a plant polyphenol, ameliorates renal concentrating ability via up-regulation of renal AQP 2 water channel in rats with cisplatin-induced ARF.…”
Section: Discussionmentioning
confidence: 99%